Detoxification from alcohol at home managed by general practitioners. Issue 6522 (15th March 1986) - Stockwell, T; Bolt, E; Hooper, J
Abstract : General practitioners have an important role in identifying and responding to problem drinkers, but no study has attempted to document their use of detoxification at home. A questionnaire was mailed to all general practitioners in Exeter Health District (n = 168) that was concerned with how they managed patients who presented with problems related to alcohol. The 145 (86%) responses showed that collectively they were identifying many more cases of problem drinking than any other local treatment agency. Of the estimated 230 patients a year for whom detoxification was arranged, half were managed at home, 40% in a local psychiatric hospital, and 9% in a local general hospital. Of those who were managed at home, 38% were unsupervised, a close relative held the medication for 45%, and 17% were supervised by a nurse. Fifty six percent (81) of doctors favoured chlormethiazole (Heminevrin) treatment, and many (17%) were prepared to prescribe this for longer than 10 days. Three quarters of the respondents thought that there was a need for specialist community services, such as community alcohol teams, to support general practitioners by supervising detoxification at home.